2022
DOI: 10.3390/pharmaceutics14112477
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Properties of a New Nanocomplex of Selenium with Taxifolin in the Cells of the Cerebral Cortex Exposed to Ischemia/Reoxygenation

Abstract: The neuroprotective effect of the natural antioxidant taxifolin (TAX) is well known for ischemic pathologies. However, the limitations of taxifolin application are described—poor solubility, low ability to penetrate the blood–brain barrier, and side effects from high doses for stroke therapy. We proposed the problem of targeted delivery of taxifolin and achievement effective concentrations could be solved by developing a nanocomplex of selenium nanoparticles (SeNPs) with taxifolin (Se–TAX). In this study, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Given that the NASH pathogenesis is heterogenous and diverse in humans, these pleiotropic effects of Taxifolin may be advantageous for clinical practice. In this respect, recent studies developed a novel nanocomplex of selenium with sorafenib [ 42 ] or Taxifolin [ 43 ], which exhibits more beneficial effects than those of single molecules in vitro in terms of anticancer or neuroprotective effects. Accordingly, the use of the nanocomplex would be a valuable therapeutic option for NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the NASH pathogenesis is heterogenous and diverse in humans, these pleiotropic effects of Taxifolin may be advantageous for clinical practice. In this respect, recent studies developed a novel nanocomplex of selenium with sorafenib [ 42 ] or Taxifolin [ 43 ], which exhibits more beneficial effects than those of single molecules in vitro in terms of anticancer or neuroprotective effects. Accordingly, the use of the nanocomplex would be a valuable therapeutic option for NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study was conducted and published in our laboratory that showed that selenium nanoparticles can have a cytoprotective effect on neuroglial cells of the cerebral cortex during ischemia/reoxygenation [48]. At concentrations as low as 3 µg/mL, selenium nanoparticles inhibit the hyperproduction of ROS in cells.…”
Section: Cytotoxicity To Eukaryotic Cellsmentioning
confidence: 99%
“…At concentrations as low as 3 µg/mL, selenium nanoparticles inhibit the hyperproduction of ROS in cells. The experiments also used a complex of selenium NPs with taxifolin (a flavonoid that lacks the "high dosage effect" that occurs in selenium NPs), while at a concentration of 10 µg/mL, the Se-TAX complex inhibits ROS hyperproduction and does not have toxicity on brain cells [48].…”
Section: Cytotoxicity To Eukaryotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TAX was able to counteract the toxicity of DEHP on cardiomyocytes by attenuating apoptosis [ 33 ].The low solubility and difficulty in absorption and digestion of this medication limit its bioavailability and effectiveness. To overcome these limitations, various nanoparticles, such as metal nanoparticles, liposomes, and inorganic nanoparticles, have been developed as tumor-targeting carriers for targeted drug delivery [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%